Reconfigurable Bandwidth and Tunable Dual-Band Bandpass Filter Design for Ultra-Wideband (UWB) Applications. Issue 6 (17th August 2016) - Alqaisy, Mushtaq A.; Chakrabraty, C.; Ali, J.; Alhawari, A. R. H.; Saeidi, Tale
ABSTRACT: Four square ring resonators together with an L-shaped uniform open tuning stub is the base of an ultra-wide bandpass filter. Based on the bandpass-coupled edge, a small gap was created in the feed lines of the proposed bandpass filter to obtain a second lower band. This study introduces a dual-band bandpass filter. The main advantage of this bandpass filter is its capability to reconfigure bandwidth and tune the center frequency of a dual-band bandpass filter function. The microstrip bandpass filter is reconfigured into a dual band when varactor diodes are fixed on the head of each uniform stub. The roll-off is characterized by sharp edges of 81.325 and 80.165 GHz/dB, which provided this filter with high selectivity in the transmission band, a wide stopband of more than 2 GHz in both sides, and a rejection band of up to 32 dB. Results show better performance of S 21, which fluctuated from 4 to 1.5 dB within the transmission band from 8.327 to 13.942 GHz. All the reported filters were modeled, and their corresponding responses were assessed by using CST Microwave Studio (CST, 2010). Measured and simulated results of the proposed bandpass filters were compared, and the results indicate good agreement.